Parametric design thinking: A case-study of practice-embedded architectural research. (September 2017) - Bhooshan, Shajay
Abstract : The paper highlights aspects of a particular parametric design thinking (PDT) distilled from practice. It describes the components of PDT – cognitive model, design method and information processing model – that are critical to an efficacious, collaborative search for solutions to architectural problems. The aspect related to the information processing model is afforded a detailed examination, synthesising the state-of-the-art in practice and research. Lastly, case studies spanning six years trace the transfer of methods and knowledge from collaborations and prototypes into projects of Zaha Hadid Architects Computation and Design group (ZHCODE). These exemplify the role of a shared language of geometry and several process related aspects of parametric design critical to its success. Highlights: Parametric design thinking (PDT) as a computationally augmented, solution oriented design thinking . Practice embedded architectural research (PEAR). Cumulative PEAR leads to a successful directed search of design-space. Cumulative PEAR enables collective problem solving.